2021
DOI: 10.3390/nano11102596
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Effect of Synthesis Conditions on the Structural, Optical, and Antibacterial Properties of Cerium Oxide Nanoparticles

Abstract: Cerium oxide nanoparticles were prepared by a precipitation method using Ce(IV) sulphate as precursor dispersed in glycerol with varying synthesis parameters such as temperature or precipitating agent. The structural and morphological characteristics of the obtained nanoparticles were investigated by X-ray diffraction, transmission electron microscopy, and diffuse reflectance spectroscopy. The crystallite size of the nanoparticles varied between 13 and 17 nm. The presence of Ce3+ and Ce4+ was proved by XPS dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 69 publications
(81 reference statements)
3
17
0
1
Order By: Relevance
“…These values are comparable to those of some earlier reported data for pure cerium oxide or doped cerium oxide nanoparticles [11,43,55,56]. From our XPS analysis, the development of oxygen vacancies on the nanostructure surface and the presence of Ce 3+ ions were confirmed [42]. In this way, the ferromagnetic behavior of the CeO-1 sample may have been the result of interactions between oxygen vacancies and Ce 3+ ions which determine the alignment of spins in the local environment.…”
Section: Magnetic Propertiessupporting
confidence: 90%
See 4 more Smart Citations
“…These values are comparable to those of some earlier reported data for pure cerium oxide or doped cerium oxide nanoparticles [11,43,55,56]. From our XPS analysis, the development of oxygen vacancies on the nanostructure surface and the presence of Ce 3+ ions were confirmed [42]. In this way, the ferromagnetic behavior of the CeO-1 sample may have been the result of interactions between oxygen vacancies and Ce 3+ ions which determine the alignment of spins in the local environment.…”
Section: Magnetic Propertiessupporting
confidence: 90%
“…In the case of CeO-3, the mixed ferromagnetic and paramagnetic phase indicated that the presence of the adsorbed oxygen decreased the oxygen deficiency and lowered the antioxidant properties. XPS studies also proved that even though CeO-1 had a lower content of Ce 3+ than CeO-3, the former was oxygen deficient while the latter was rich in oxygen, i.e., with an oxygen content higher than stoichiometric value [42]. The oxygen deficient sites in CeO-1 were the active sites that increased the possibility of Ce 3+ oxidation, thereby also increasing the scavenging ability of the sample as compared to CeO-3.…”
Section: Antioxidant Activitymentioning
confidence: 85%
See 3 more Smart Citations